CUSTOMER ENGAGEMENT IMPACTS TOWARDS PURCHASE INTENTIONS IN THE ONLINE TRAVEL AGENT INDUSTRY - Nicks Candra Putra; Carolin Carolin; Gabriel Jessye; Isaiah Abib; Michael Laurel (Jurnal Administrasi Bisnis, 2020)
This study attempts to investigate the effect of customer engagement which represented through surveillance, social interaction, sharing information, attraction, and social influence on OTA‟s (Online Travel Agency) customer engagement in social media such as Facebook, Twitter, and Instagram about its connection to purchase intention. The importance of this research is to understand the customer engagement level necessary to satisfy the needs of social media users that can lead to purchase intentions. The questionnaires used convenience sampling with totals of 30 questions and 200 respondents within the scope of Java Island Indonesia. Partial Least Square was used to analyze the data and six hypotheses were tested with five independent variables which are surveillance, social interaction, sharing information, attraction, and social influence. One mediating variable which is customer engagement, and one dependent variable purchase intention. The findings of this research are showing that OTAs are better if they focus on social influence, social interaction, and sharing information to increase customer engagement and ultimately create the intention to purchase for customers.